2009
DOI: 10.1002/bem.20546
|View full text |Cite
|
Sign up to set email alerts
|

No effects of mobile phone use on cortical auditory change‐detection in children: An ERP study

Abstract: We investigated the effect of mobile phone use on the auditory sensory memory in children. Auditory event-related potentials (ERPs), P1, N2, mismatch negativity (MMN), and P3a, were recorded from 17 children, aged 11-12 years, in the recently developed multi-feature paradigm. This paradigm allows one to determine the neural change-detection profile consisting of several different types of acoustic changes. During the recording, an ordinary GSM (Global System for Mobile Communications) mobile phone emitting 902… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 53 publications
(59 reference statements)
0
10
0
4
Order By: Relevance
“…Preattentive auditory discrimination processing (and short-term memory) reflected by mismatch negativity (MMN) was not affected by a GSM signal in adults [Kwon et al, 2009] or children [Kwon et al, 2010a]. Kleinlogel et al [2008b] and Stefanics et al [2008] found no effects of UMTS signals on auditory discrimination processing in oddball tasks.…”
Section: Sleep Eeg As Shown Inmentioning
confidence: 95%
“…Preattentive auditory discrimination processing (and short-term memory) reflected by mismatch negativity (MMN) was not affected by a GSM signal in adults [Kwon et al, 2009] or children [Kwon et al, 2010a]. Kleinlogel et al [2008b] and Stefanics et al [2008] found no effects of UMTS signals on auditory discrimination processing in oddball tasks.…”
Section: Sleep Eeg As Shown Inmentioning
confidence: 95%
“…The argument against a causal influence of RF EMF exposure on cognitive function and CNS in children is also based on three studies [41,42,45]. In their experimental study, Haarala et al [45] used several cognitive tests to measure the effect of RF EMF exposure on memory, reaction time, and vigilance.…”
Section: Cognitive Effects and Cns Effects: Pro-and Con-argumentsmentioning
confidence: 98%
“…There are seven original papers addressing the effect of RF EMF on cognitive function and CNS in children [38][39][40][41][42][43][44]. The age of the children investigated in these studies was in the range of 10-17 years.…”
Section: Cognitive Effects and Cns Effects: Pro-and Con-argumentsmentioning
confidence: 99%
“…Ponieważ ucho sąsiaduje ze źródłem PEM, którym jest telefon komórkowy, więk-szość badań ukierunkowywano na sprawdzenie oddziaływania PEM na układu słuchowy, w tym na słu-chowe potencjały wywołane -w trakcie lub po ekspozycji, a nawet po ekspozycji wielokrotnej. Nie zaobserwowano w tych badaniach żadnych skutków oddziały-wania PEM [37][38][39][40][41][42][43][44][45][46]. Również badania na zwierzętach nie wykazały takiego oddziaływania [47].…”
Section: Wpływ Pem Na Potencjały Wywołaneunclassified